Multiple Quantum Wells for P T -Symmetric Phononic Crystals - Poshakinskiy, A.V. (2016)
We demonstrate that the parity-time symmetry for sound is realized in laser-pumped multiple-quantum-well structures. Breaking of the parity-time symmetry for the phonons with wave vectors corresponding to the Bragg condition makes the structure a highly selective acoustic wave amplifier. Single-mode distributed feedback phonon lasing is predicted for structures with realistic parameters.